2017
DOI: 10.1186/s12880-017-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

Superb microvascular imaging (SMI) compared with conventional ultrasound for evaluating thyroid nodules

Abstract: BackgroundSuperb microvascular imaging (SMI) for depiction of microvascular flow in thyroid nodules was compared with color/power Doppler imaging (CDI/PDI) and contrast-enhanced ultrasonography (CEUS). In addition, the diagnostic performance of conventional ultrasound combined with SMI for differentiating benign and malignant thyroid nodules was evaluated.MethodsPreoperative conventional ultrasound consisting of gray-scale ultrasonography and CDI/PDI, followed by SMI and CEUS, was used to record 52 thyroid nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 14 publications
2
71
0
1
Order By: Relevance
“…15 Superb Microvascular Imaging provides useful information for both qualitative and quantitative analysis compared with PDUS. [16][17][18][19] It has both color and monochromatic modes of vascular imaging. The color mode displays B-mode and color information simultaneously and facilitates a time-smoothing function control, which results in accurate visualization of vessel continuity.…”
Section: Vascular Pattern Analysis Using Power Doppler Ultrasound (Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Superb Microvascular Imaging provides useful information for both qualitative and quantitative analysis compared with PDUS. [16][17][18][19] It has both color and monochromatic modes of vascular imaging. The color mode displays B-mode and color information simultaneously and facilitates a time-smoothing function control, which results in accurate visualization of vessel continuity.…”
Section: Vascular Pattern Analysis Using Power Doppler Ultrasound (Pdmentioning
confidence: 99%
“…The unique algorithm separates flow signals from motion artifacts and clutter and consequently enables visualization of very low‐velocity microvascular flow in LNs that is not usually attainable with PDUS . Superb Microvascular Imaging provides useful information for both qualitative and quantitative analysis compared with PDUS . It has both color and monochromatic modes of vascular imaging.…”
mentioning
confidence: 99%
“…Assessment of thyroid malignancy based on intranodular and peripheral vascularity detected using Doppler ultrasound has been attempted by several researchers [2][3][4][5][6][7][8][9][10][11] . However, large tissue motion in unavoidable in thyroid imaging due to its proximity to the pulsating carotid artery -a major challenge in reliably imaging small vessel blood flow.…”
mentioning
confidence: 99%
“…35 A further study compared SMI with CDFI and CEUS for depicting microvascular flow in thyroid nodules and found that the accuracies of conventional US combined with CDFI, SMI, and CEUS for predicting malignancy were 67.31%, 86.54%, and 92.31%, respectively. The accuracy of SMI differed significantly from the accuracy of CDFI but not CEUS, 36 indicating that SMI may be a more economical method of depicting the microvasculature in thyroid nodules. Using SMI can prevent adverse reactions associated with the contrast agents used in CEUS, although the frequency of these reactions is relatively low.…”
Section: Superb Microvascular Imaging For Evaluating Thyroid Nodulesmentioning
confidence: 82%